Knowledge, attitude and practice regarding screening and managing diabetic microvascular complications among general practitioners of community health centres: a cross-sectional study in Shanghai, China - Hua Yang; Jian Gao; Ying Yu; Cuiling Huang; Chengdian Lan; Zhangyan Chen (BMJ Open)
Objective To evaluate the knowledge, attitude and practice (KAP) regarding screening and managing diabetic microvascular complications, encompassing diabetic retinopathy (DR), diabetic kidney disease (DKD) and diabetic neuropathy (DN), among general practitioners (GPs).Design Cross-sectional study.Setting The online questionnaire survey was conducted between April and July 2023.Participants GPs from community health centres (CHCs) in all 16 districts of Shanghai were recruited.Primary and secondary outcome measures The data of sociodemographic characteristics, KAP scales, training experience and screening instruments for community screening and managing diabetic microvascular complications were collected. Multiple stepwise linear regression was used to explore the influencing factors of KAP. Restricted cubic spline curves with four knots (5%, 35%, 65%, 95%) were used to determine the association between KAP score and duration of general practice.Results A total of 1243 questionnaires were included in the analysis. The total KAP score was 66.6±8.8/100, and the knowledge, attitude and practice scores were 64.7±8.7, 83.5±10.5 and 51.6+17.8, respectively. Male (β=−2.419, p=0.012), shorter practice duration (β=−1.033, p=0.031), practice in rural area (β=3.230, p=0.001), not attending training in diabetic microvascular complications (β=−6.346, p<0.001), not managing diabetic patients (β=−4.503, p<0.001), less number of diabetes patients under management (β=−0.007, p=0.035), less number of screening instruments based on self-report of GP (β=−1.681, p<0.001), lower knowledge score (β=−0.190, p<0.001) and lower attitude score (β=−0.414, p<0.001) were associated with lower practice score of GPs. The KAP total score increased with the working years of general practice; however, this effect was no longer observed in knowledge score after 15 years, while the attitude and practice scores showed a continuously increasing trend.Conclusions GPs showed insufficient knowledge and poor clinical practice on screening and managing diabetic microvascular complications. There is an urgent need to improve their capacity to provide better care for those with diabetic microvascular complications through targeted training.